A comparison of paddle forces between whitewater and flatwater training in C1 canoe slalom - Wakeling, J. M.; Smiešková, S.; Vajda, M.; Busta, J. (Journal of Functional Morphology and Kinesiology, 2024)
Background/Objectives: Becoming an elite canoe slalom athlete requires thousands of hours of training, spread over many years. It is difficult to assess the correct balance between flatwater and whitewater training because differences in the paddle forces on these terrains are not known. The aim of this study was to describe paddle forces during canoe slalom training on flatwater and whitewater courses for the C1 canoe category.